Information and Conferences - Editorial Board, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
“Maritime silk road” and international relations in the South China Sea: Present situations and prospectsIt was the name of the international conference co-hosted by VNU-USSH and Konrad Adrenauer Stiftung (KAS) at Hilton hotel (Hanoi) from November 26th to 27th 2015 with the participation of domestic and foreign prestigious scholars. The conference aims at discussing about “Maritime silk road” and its implications with the current political and security situation in the region and the world.The prominent domestic and foreign scholars included Dr. Xue Li (Institute of World Economics and Politics, China Academy of Social Sciences); Prof. David Arase (Johns Hopkins University); Prof. Sejichiro Takaji (Japan Institute of International Affairs); Dr. Nguyen Thanh Minh (Vietnam Coast Guard, Ministry of Defense); Assoc. Prof. Dr Nguyen Thi Lan Anh (Vietnam Academy of Foreign Affairs). Speaking at the conference, Mrs. Rabea Brauer said: “A conference on the “maritime silk road” was organized last year. Today we continue to discuss its implications on the policy and security situation in each region. We have invited here leading speakers and they are going to exchange their views on the situation and prospects of the maritime silk road on the regional and world security and political situation".Meanwhile, Assoc. Prof. Dr Pham Quang Minh emphasized the direct impact of the “Maritime silk road” on Vietnam and Southeast Asia:  “There have been great changes among ASEAN and the big question is how we are going to respond to these changes. China’s rise is most important among these changes.“One belt-one road” is the policy of Chinese leaders in approaching economies and rapidly connecting land and maritime routes that link Asia and the Middle East and Europe. China’s rise influences the Strategy to reorganize the world; changing its landscape and creating lasting impact on the Asian situation”.At the first section, Dr. Xue Li presented her paper “How does OBOR Strategy Facilitate Sino-ASEAN Ties?” to the conference, in which she remarked that the “One belt-one road” policy would be a “crucial strategy” in China’s foreign policy in the coming decade and ASEAN would likely be its first litmus test. Another paper titled “Historical approach to the origins of maritime silk road” by Dr. Trinh Van Dinh (VNU-USSH) attempted to address the introduction of “maritime silk road” from political and historical perspective to sketch out the hegemonic ambitions of Chinese kings. Both papers opened up lively discussions between scholars, as many questions were raised for Dr. Xue Li on the Sino-China relations. The questions were responded adequately and scientifically.The conference is divided into six panels: Remarks on the “Maritime silk road” of China; Perspectives from the navies; The tension in South China Sea; ASEAN’s perspectives and stances; Perspectives and stances and cooperation in the region; and Round table - Current situation in foreign affairs.  The full papers are being collected for publish in the Journal of Social Sciences and Humanities, and in a reference book by one international publisher."International Conference - Researching and Teaching German ideology in universities"On November 12th, 2015 the Institute of Contemporary Religious Studies, Faculty of Philosophy (VNU-USSH), collaborated with the Institute for Religious Science (Germany) to organize the international seminar titled "Researching and teaching German thoughts in the universities ". The workshop took place from 12th to the end of 13th of November, 2015. Attending the seminar were PhD. Harald Hermann, Director of the Institute of Religious Science, Germany; Dr. Anke Stahl, DAAD; Ms. Chuong Phuong, representative of the UNESCO National Commission, Ministry of Foreign Affairs; Prof. Dr. Nguyen Van Kim, Vice Rector of VNU-USSH and numerous scholars from Germany, Taiwan, the USA, Austria, Indonesia and Vietnam.The workshop took place within the framework of long-term scientific activities annual of Research contemporary religion Center, VNU-USSH. Germany is home to many renowned scientists in the fields of natural sciences and social sciences. Though geographically distant, the exchanges between Vietnam and Germany began at an early time. There have been many works by Vietnam scientists that study the development of diverse and rich philosophical thoughts of Germany in particular and Europe in general. Many works and articles make in-depth analysis of the values and aesthetics of German ideas and their contribution to Vietnamese philosophy. Beside the achieved facets, it should be noted that the study of German thoughts in Vietnam for many different reasons has not kept up with the desired expectations, especially the study and teaching on German thinkers in the fields of theology and religious studies.The workshop is an opportunity for domestic and foreign scientists to discuss and address the contents of German thoughts and the study and teaching of German ideas at Vietnamese universities, which can open up new avenues for future research. The workshop was divided into three main panels: Panel 1- metaphysical philosophy, epistemology, ethics, aesthetics, social philosophy; Panel 2- theological matters and religious studies; Panel 3-the practical influences of German thoughts- teaching German thoughts at universities."International scientific seminar on the country's development policy"On 30 October 2015 in Fortuna Hotel (Hanoi), the VNU-USSH and Rosa Luxemburg Institute (Germany) coordinated to hold the International Scientific Conference titled: "Leftist theories in national development: Experience sharing among Vietnam, Germany and Latin America countries".This is one of the activities between Rosa Luxemburg Foundation and the Institute of Policy and Management of the USSH within a project named "Choosing the Leftist theories in a changing world". Participants at the seminar included Mrs. Liliane Danso-Dahmen-Director of Rosa Luxemburg Foundation in Southeast Asia; Prof.Dr. Nguyen Van Khanh - Rector of USSH, Director of the Institute of Policy and Management; and Ambassadors of Latin America countries to Vietnam such as Cuba, Chile, Venezuela, Brazil, Colombia and Mexico. Speaking at the seminar, Prof. Dr. Nguyen Van Kim-Vice Rector of VNU-USSH said: "The development of the Left movement and its regional and global impact has been a big issue in most Latin America countries and many nations of the world. It is both a challenge and an opportunity in the development of each country and region, including Germany, Latin America and Vietnam. "He also hoped that “international and Vietnamese researchers and experts continue to examine and clarify the guidelines and policies; and their motivation, effectiveness, scope and degree of impact; at the same time there are lessons to be learned from the various realities of each country, which is a basis for development policies and enhancing opportunities for bilateral and multilateral cooperation between countries today".The seminar discussed about "Leftist theories" and the national leadership of "Left Parties" with presentations revolving around three subjects: Vietnam, the Federal Republic of Germany and Latin America countries (Socio-economic achievements of Venezuela under the leadership of the left Party in 15 years by Mrs. Katiuska her Maestre - Charge d'affaires ad interim of Venezuela's embassy in Vietnam, ...).Rosa Luxemburg Foundation has supported and coordinated with the University of Social Sciences and Humanities in the "Choosing the Left theories in a changing world" project for over 6 years (2009-2015). There have been many academic activities successfully held through annual international seminars (2009, 2010, 2011, 2012, 2013) such as "Leftist rationale from the Marxist viewpoint" seminar (November 2010) and most recently an international seminar named "The role and contribution of the state in the development of Vietnam and Cuba" in October 2014."Building the specific mechanism and policy for tourism in the North Western area"This workshop was taken by the cooperation between the Faculty of Tourism, VNU-USSH and Association of Vietnamese Folklorists on 19/12/2015. There were 50 scholars and activists participated in the conference to discuss the specific topics of criteria for building the ecotourism model in this area; making the compatible mechanism and policy on developing the community tourism; setting up the suitable standards and criteria for ecotourism in Vietnam, etc. The North Western area of Vietnam includes 10 provinces with plentiful natural landscapes and rich traditional values, customs and habits. This land also involves a large number of minority groups, and the significant revolutionary base during the war time against French. These conditions also make the significant advantages for the development of ecotourism in this area toward the sustainable development.As keynote speaker, Prof To Ngoc Thanh, President of the Association of Vietnamese Folklorists suggested the policy implications for ecotourism development in this area as "The State should makes policies for ecotourism development or deals with some problems in terms of conserving, sustaining and developing the tourism in the North Western". In the same idea to develop the ecotourism sustainably in this area, Dr Nguyen Anh Tuan also focused on four criteria, as sustaining the ecosystem, conserving and suitably exploiting the indigenous cultural values, organizing the education activities related to the environment and ecosystem, and organizing the ecotourism activities with community participation. Other presentation by Dr Duong Van Sau also pointed the ideas on localizing the tourism economic to each local area, and required the comprehensive policies for tourism development; and selecting and making the significant tourism spots and linkages among local areas...Many ideas of scientists, experts, leaders of the Provincial Departments of Culture, Sports and Tourism gave the exchange, discussion and sharing the knowledge, experience, ideas to develop specific mechanisms and policies to construct the suitable ecotourism for the North West of Vietnam.